Various Diseases and Clinical Heterogeneity Are Associated With “Hot Cross Bun” - Zhu, Shuzhen; Li, Hualing; Deng, Bin; Zheng, Jialing; Huang, Zifeng; Chang, Zihan; Huang, Yanjun; Wen, Zhibo; Liang, Yanran; Yu, Mengjue; Chan, Ling-Ling; Tan, Eng-King; et al. (Frontiers in Aging Neuroscience, 2020)
Abstract Objective To characterize the clinical phenotypes associated with the ‘hot cross bun’ sign (HCBs) on MRI, and identify correlations between neuroimaging and clinical characteristics. Methods Firstly, we screened a cohort of patients with HCBs from our radiologic information system (RIS) in our center. Secondly, we systematically reviewed published cases on HCBs and classified all these cases according to their clinical heterogeneities. Finally, we characterized all HCBs cases in detail, classified the disease spectra and their clinical heterogeneity. Results Out of a total of 3546 patients who were screened, we identified 40 patients with HCBs imaging sign in our cohort; systemic literature review identified 39 cases, which were associated with 14 diseases. In our cohort, inflammation (neuromyelitis optica spectrum disorders (NMOSD), multiple sclerosis (MS) and acute disseminated encephalomyelitis (ADEM)) and toxicants (toxic encephalopathy caused by phenytoin sodium (TEPS)) were some of the underlying etiologies. Published cases by systemic literature review were linked to metabolic abnormality, degeneration, neoplasm, infection and stroke. We demonstrated that the clinical phenotype, neuroimaging characteristics and HCBs response to therapy varied greatly depending on underlying etiologies. Conclusion This is the first to report HCBs spectra in inflammatory and toxication diseases. Our study and systemic literature review demonstrated that the underpinning disease spectrum may be broader than previously recognized.